Investigation of effects of rehydration of cement in recycled crushed concrete road base - Deilami, Sahar (Curtin University, 2014)
This research investigates the methods controlling shrinkage cracking of Recycled Crushed Concrete (RCC) and RCC blended with two recycled aggregate types, namely, brick & tile and ferricrete, for road base whilst retaining the inherent strength of the base material. The strength tests on the various blends indicated that with the addition of brick & tile or ferricrete to RCC, the resulting materials remained "stiff'. In conclusion, using recycled materials can enhance heavy duty pavement behaviour.